Family Empowerment Post (Posdaya) In Social Relation Perspective In Community Empowerment - Meiriki, Andri (International Journal for Educational and Vocational Studies, 2019)
Poverty is one of the social problems which requires teamwork and synergy to counter it. Poverty is not only the government's responsibility but also other stakeholders. Damandiri Foundation takes a role to help counter measuring poverty through community empowerment concept by initiating the establishment of Family Empowerment Post (Posdaya). Posdaya is not only associated with material or economic aspect but also with social relation intended to build through this Posdaya so that this program can be sustainable among the society. The purposes of the present study were: 1) to find out the role of parties involved in community empowerment through Posdaya, and the social relation built among the stakeholders; 2 ) to find out the pattern of synergy in the attempt of developing Posdaya to be sustainable community empowerment program. The present study employed qualitative approach, this approach was employed to obtain an in-depth understanding of the implementation of Posdaya program initiated by Damandiri Foundation. The result of the study shows that the stakeholders, especially Damandiri Foundation, Government, especially regional government, Universities, and Private sectors should maintain their involvement to continue and support Posdaya, especially the established ones, and develop communication network pattern that allows all parties to take active participation in developing Posdaya.